Analysis of the Application of Planning Functions on the Development of the State Civil Apparatus in Fakfak District Office Middle East Fakfak Regency - Waromi, Agustina; Mbaubedari, Hens Fenska Marlen; Merey, Aser Yakub (Budapest International Research and Critics University, 2022)
Human Resource Planning becomes a guideline in carrying out mutations both vertically to the center and horizontally parallel to regional apparatus organizations at the Regency level in the regions and also becomes the basis for evaluating State Civil Apparatus working in the Middle East Fakfak District Office as well as other Regional Apparatus Organizations within the scope of the Fakfak Regency Government. The research method is qualitative. The results of the study show thatThe Government of Fakfak Regency in the administration of government affairs is supported by the State Civil Apparatus (ASN) which totals 4,039 people. Seen by gender, male State Civil Apparatus (ASN) amounted to 2,085 people and 1,954 women. Meanwhile, based on the level of education, there are still 71 elementary school graduates, 147 junior high school graduates, 1,164 high school graduates, 833 D1-D3 students, 1,652 D4-S1 graduates and 172 postgraduate degrees. ConclusionManagement is a combination of science and art; Management is a systematic, coordinated, cooperative, and integrated process in utilizing the elements (6M); New management can be applied if there are two or more people working together in an organization; Management should be based on division of labor, duties, and responsibilities; Management consists of several functions (Planning, Organizing, Actuating, Controlling) or POAC; Management is only a means to an end.